Exploring the determinants of consumer preference for Product-as-a-Service (PaaS) models: a case study on heating systems - Szczech-Pietkiewicz, Ewelina; Radło, Mariusz-Jan; Nadolny, Michał; Kuźmiński, Łukasz (Economics and Environment, 2025)
The study aimed to identify factors influencing the choice of Product-as-a-Service (PaaS) over ownership in customer decisions, using heating systems as a case study as an example of a less saturated PaaS market. The analysis is based on a nationwide quantitative survey of the population of users of single-family houses. An econometric model was created, describing customer choice of PaaS model by two describing decision factors and two of a financial nature. Results showed that quality, service, operating, and maintenance costs were key factors, while demographics had little impact. The text highlights research gaps in PaaS and circular economy, such as understanding consumer preferences, financial models in the built environment, factors affecting PaaS adoption for heating equipment, circular economy finance, and necessary changes in the financial sector. This research enhances consumer preference understanding and underscores PaaS potential for heating appliances.